(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the characteristics of dyslipidemia and cardiovascular risk in type 2 diabetes mellitus (T2DM) patients. Methods: A cross-sectional descriptive study was conducted on 300 T2DM outpatients at the General Examination Department - Bac Ninh Provincial Endocrinology Hospital from September 2024 to September 2025. Key research variables included lipid profiles (Total Cholesterol, Triglycerides, HDL-C, LDL-C), HbA1c, and 10-year cardiovascular risk assessment using the Framingham Risk Score (FRS). Results: The overall prevalence of dyslipidemia in the study group was 58.3%. The dyslipidemia phenotype was predominantly characterized by high total cholesterol (43.3%) and high triglycerides (32.7%). Notably, the prevalence of high LDL-C was very low (2.7%). Regarding cardiovascular risk, 10.0% of patients were stratified as high-risk and 33.3% as moderate-risk according to the FRS. For glycemic control, 71.0% of patients failed to achieve the target HbA1c < 7.0%. Analysis of associated factors identified that male gender (p=0.021) and concurrent dyslipidemia (p=0.033) were significantly associated with poorer HbA1c control compared to other groups. Conclusion: The study demonstrates a high prevalence of dyslipidemia and poor glycemic control. Dyslipidemia (especially hypertriglyceridemia) and male gender are factors associated with failing to meet glycemic targets in this patient population.